The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1088/0960-1317/12/5/306
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for determining linear thermal expansion coefficients of thin films

Abstract: In this paper we present a simple method for determining the linear thermal expansion coefficients (LTECs) of thin films using compact micromachined structures and common experimental apparatus. The structures can be fabricated by simple silicon-based micromachining techniques with one mask process and in situ along with active devices on the same chip for monitoring the LTECs of the thin film. An analytical expression is derived to relate the LTECs of thin films with the lateral displacements of microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…It has been reported that Fig. 4 Thermal expansion coefficient versus temperature (Pan 2002) this effect can generates a variation of analytical results about 10%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been reported that Fig. 4 Thermal expansion coefficient versus temperature (Pan 2002) this effect can generates a variation of analytical results about 10%.…”
Section: Discussionmentioning
confidence: 96%
“…Also, thermal expansion coefficient increase with temperature rise during micro actuator operation. The variation of thermal expansion coefficient for polysilicon is reported by Pan (2002). This report shows that polysilicon thermal expansion coefficient varies significantly over the temperature range of 450°C and higher.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The deflection is measured by using the optical interferometric technique. Pan has reported a structure composed of a pair of cantilever beams with different lengths connected by a short tip beam to measure the CTE of the thin film [13]. When the temperature changes, a large displacement of the tip beam induced by different expansions or contractions between the two cantilever beams has been observed and measured with an optical microscope.…”
Section: Introductionmentioning
confidence: 99%
“…The structures comprise of a pair of strain gauges with known Young's modulus and a cantilever beam made of the measured film. The strain gauge is similar to author' s previous works [26,27]. The detailed performance of the strain gauge can be found in reference [26].…”
mentioning
confidence: 95%